2019
DOI: 10.1177/0269881118822161
|View full text |Cite
|
Sign up to set email alerts
|

Lithium treatment for unipolar major depressive disorder: Systematic review

Abstract: Background: The potential value of lithium treatment in particular aspects of unipolar major depressive disorder remains uncertain. Methods: With reports of controlled trials identified by systematic searching of Medline, Cochrane Library, and PsycINFO literature databases, we summarized responses with lithium and controls followed by selective random-effects meta-analyses. Results: We identified 36 reports with 39 randomized controlled trials: six for monotherapy and 12 for adding lithium to antidepressan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 84 publications
2
43
0
15
Order By: Relevance
“…In his scrutiny, the author points to three main errors that seem to have affected systematically ten international guidelines, namely the Woozle effect (evidence by citation), reference inflation (inappropriate citation of pivotal, generally old, studies) and belief perseverance (inability to modify evidence‐based recommendations despite the presence of contrary data). We concur with the author that the evidence supporting the effectiveness of lithium in acute bipolar depression, and to a lesser degree also in major depressive episodes, remains inadequate . A different matter is, in our opinion, to label guidelines recommendations as inaccurate or biased, even if, as the author stated, no deceptive intentions were present.…”
supporting
confidence: 63%
“…In his scrutiny, the author points to three main errors that seem to have affected systematically ten international guidelines, namely the Woozle effect (evidence by citation), reference inflation (inappropriate citation of pivotal, generally old, studies) and belief perseverance (inability to modify evidence‐based recommendations despite the presence of contrary data). We concur with the author that the evidence supporting the effectiveness of lithium in acute bipolar depression, and to a lesser degree also in major depressive episodes, remains inadequate . A different matter is, in our opinion, to label guidelines recommendations as inaccurate or biased, even if, as the author stated, no deceptive intentions were present.…”
supporting
confidence: 63%
“…Indeed virtually all available treatments for bipolar disorder, including lithium, anticonvulsants, and antipsychotics are notably limited in their effectiveness against recurrences or acute episodes of bipolar depression and their long-term recurrences, with the exception of lamotrigine for long-term treatment (Geddes et al 2004, 2010; Poon et al 2012; Baldessarini 2013; Vázquez et al 2013; Forte et al 2015). However, some randomized, double-blind trials from the 1970s and several recent studies found that long-term treatment with lithium also may reduce recurrences in unipolar major depressive disorder (Abou-Saleh et al 2017; Tiihonen et al 2017; Undurraga et al 2019). In addition, lithium appears to have value in augmenting antidepressant treatment, especially during episodes of unipolar major depression that respond unsatisfactorily to antidepressant treatment.…”
Section: Efficacy Of Lithium Treatmentmentioning
confidence: 99%
“…In addition, lithium appears to have value in augmenting antidepressant treatment, especially during episodes of unipolar major depression that respond unsatisfactorily to antidepressant treatment. Most studies supporting this application have involved older, tricyclic antidepressants, but similar effects may occur with modern antidepressants as well (Austin et al 1991; Bauer and Döpfmer 1999; Bauer et al 2003; Alevizos et al 2012; Bauer and Gitlin 2016; Undurraga et al 2019). Finally, it has been suggested that lithium occurring naturally in drinking water may lower the incidence of dementia, but this finding needs to be verified (Kessing et al 2017a, b).…”
Section: Efficacy Of Lithium Treatmentmentioning
confidence: 99%
“…Some clinicians are skeptical about the effectiveness of lithium in unipolar depression (22,23), but a recent meta‐analysis of 39 randomized clinical trials (23) supports such efficacy. Lithium was superior to placebo as an augmentation agent (odds ratio, OR: 2.5; number need to treat, NNT: 4.9) and superior to placebo for treatment‐resistant depression (OR: 3.1).…”
Section: Clinical Indicationsmentioning
confidence: 99%